SURVEI KEPUASAN MASYARAKAT SEBAGAI TOLOK UKUR KEBERHASILAN IMPLEMENTASI PELAYANAN PUBLIK DALAM MENCAPAI GOOD GOVERNANCE DI POLITEKNIK MANUFAKTUR BANDUNG - Ariyani, Emma Dwi; Sadikin, Supriyadi; Muhammad, Achmad (LPPM STIE Muhammadiah Bandung, 2023)
This study aims to measure customer satisfaction with the services provided by Polman Bandung. The method used in this research is quantitative analysis with measurements using the Likert scale method, to obtain the value of the Community Satisfaction Survey (SKM) service unit a weighted average value approach is used with the total formula of the perception value per element divided by the total elements filled in multiplied by the weighting value. The dimensions measured consist of 9 CHARACTER dimensions, namely: compliance, complaint handling, assurance, reliability, service ability, clarity, tangible, empathy, and responsiveness. The results of the validity and reliability tests of the measurement instruments show that the instruments are valid and reliable so that the measurement instruments can be used properly. The number of respondents in this study was 757 people. The work units measured were 8 service units in Polman Bandung. The conclusion of the measurement results shows that the total score for measuring satisfaction with services at Polman Bandung is 75.39, which means the Good category, with the lowest value being the tangibility dimension (physical evidence) with an IKM of 2.93 and being the main priority for making improvements, while the ability to serve dimension (ability to provide services) with the highest IKM value of 3.08 and being the last priority for making improvements. The follow-up improvement plan can be carried out with priorities starting from the element with the least good results and arranged for the short, medium, or long term in achieving good governance in Polman Bandung.